The Homebrewed Christianity guide to the Holy Spirit : hand-raisers, Han, and the Holy Ghost - Kim, Grace Ji-Sun, 1969- (Homebrewed Christianity guide., 2018)
It is time for the Holy Spirit to get its own street cred! In this guide to the Spirit, Kim is putting the Holy Ghost back where it belongs; after all, the Spirit gave birth to the church and kept it rocking, rolling, revivaling, and transforming across time and culture. Throughout the book, you will get a taste of the different ways the church has understood the Spirit, partnered with the Paraclete, and imaged the Spirit in scripture. Kim brings together the tradition with contemporary culture, science, and the global church.